Velocity‐resolved Laser‐induced Desorption for Kinetics on Surface Adsorbates. Issue 5 (2nd May 2022) - Pappendorf, Kim; Golibrzuch, Kai; Zhong, Tian‐Li; Schwabe, Sven; Kitsopoulos, Theofanis; Wodtke, Alec M.
Abstract: Invited for this month's cover are the groups of Alec M. Wodtke at the Georg‐August University in Göttigen (Germany) and at the University of Crete (Greece). The cover picture shows ammonia (NH3 ) molecules adsorbed on an atomically flat platinum surface. An ultra‐short laser pulse hits the surface and heats up the metal electron rapidly to several thousand Kelvin within a few 100 fs. This high electronic temperature causes a fraction of the ammonia molecules to desorb with hyperthermal velocity from the surface. Depended on the laser intensity, the number of desorbing molecules is proportional to the surface coverage. Read the full text of their Research Article at 10.1002/cmtd.202200017 . Abstract : "… Consequently, our basic idea was to find a way to transfer surface species into the gas‐phase where we have extremely sensitive techniques to detect them…" Find out more about the story behind the front cover research at 10.1002/cmtd.202200017 .